FROM CHRONOLOGICAL NETWORKS TO BAYESIAN MODELS: CHRONOLOG AS A FRONT-END TO OXCAL. Issue 1 (14th February 2022) - Levy, E; Piasetzky, E; Fantalkin, A; Finkelstein, I
ABSTRACT: We present a new method for creating an OxCal Bayesian model that bypasses the complex task of writing OxCal code. Our methodology employs the recent ChronoLog software as a graphical front-end for generating OxCal scripts. This approach enables archaeologists to create complex Bayesian models—including termini post and ante quem, duration bounds and synchronisms—with the help of a user-friendly interface. The target audience can be divided into beginners, who might struggle to create chronological models using OxCal directly, and experienced OxCal users, who should find that ChronoLog saves time when coding complex models. Three case-studies from recent publications are presented.